Assessing the usefulness of B-mode and colour Doppler sonography, and measurements of circulating progesterone concentrations for determining ovarian responses in superovulated ewes - Oliveira, M. E. F. [UNESP]; Ribeiro, I. F. [UNESP]; Rodriguez, M. G. K. [UNESP]; Maciel, G. S. [UNESP]; Fonseca, J. F.; Brandao, F. Z.; Bartlewski, P. M. (Wiley-Blackwell, 2018)
Contents The main goal of this study was to assess the usefulness of two imaging modalities, namely the B-mode and colour Doppler sonography, and serum progesterone (P-4) concentrations for determining the ovarian response in superovulated ewes. Twenty-four sexually mature Santa Ines ewes underwent the superovulatory treatment consisting of eight injections of porcine FSH (total dose of 200 or 133 or 100mg; n=8 ewes/total dose) given at 12-hr intervals and initiated 48hr before CIDR (R) (Pfizer Inc., Auckland, New Zealand) removal. Six days after natural mating, the ovaries of all donor ewes were visualized and examined with transrectal ultrasonography and then with videolaparoscopy to identify and enumerate corpora lutea (CL) and luteinized unovulated follicles (LUFs). Jugular blood samples were collected just prior to ovarian examinations. The total number of CL (r=.78 and 0.83, p<.0001) and LUFs (r=.74 and 0.90, p<.0001) enumerated using the B-mode and colour Doppler ultrasonographic technique, respectively, were correlated with that ascertained by videolaparoscopy. Circulating concentrations of P-4 were related directly to the number of healthy CL (r=.73, p=.0002) and inversely to the number of prematurely regressing CL (r=-.46, p=.03), but the accuracy of predicting the number of short-lived CL with serum P-4 concentrations was very poor. The present results indicate that ultrasonographic imaging and serum P-4 measurements on the day of embryo recovery are useful indicators of total/normal CL numbers and both ultrasonographic techniques can be used to quantify LUFs in superovulated ewes.
Keywords: laparoscopy; luteal structures; ovary; progesterone; Santa Ines ewes; superovulation; ultrasonography